Sarcastic Utterance in Mel Gibson™s Movie Hacksaw Ridge - Sinaga, Basar Jenius; Bahri, Syamsul (Universitas Negeri Medan, 2023)
The goal of this study is to identify the types and purposes of sarcasm obtained from the characters in the Mel Gibson film Hacksaw Ridge. specifically found twelve characters whose words often contain sarcastic remarks in the film. This study uses qualitative research to explain linguistic information on the use and varieties of sarcastic language in the Mel Gibson film Hacksaw Ridge. The dialogue in the movie Hacksaw Ridge served as the study data source. By using the theories of Keraf (1999) to examine the function of sarcasm and Elizabeth Camp (2011) to examine the form of sarcasm, the equivalent technique was applied to the examined data. According to the results, propositional sarcasm, which has 12 utterances (24%), is the most common type of sarcasm, followed by like prefix sarcasm, which has 16 utterances (32%), illocutianary sarcasm, which has 11 utterances (24%), and lexical sarcasm, which has 11 utterances (20%). From the result it was found the most dominant one is Like Prefix Sarcasm. And finally sarcasm was used in the film becaus it is a war movie, the movie has a high emotional intensity, which leads to some sarcastic or angry statements.